Sweet On'D - Omar, Rahman; Arifin, Ainun Mardiah; Shane D. Nelson, Geena; Abdul Rahman, Amal Nur Hurul Ain; Juanis, Jenneviera (2013)
Onde-onde is a business that deals with variety cake industry in Malaysia. Due to we are the first that produced this kind of product, we come out with "Sweet On'D". By walk-in to our "Sweet On'D" outlet, customer will be serve better service and experience wonderful moment once enjoying our product. The name of 'Sweet On'D' comes from the product that we want to sell that traditionally called as 'onde-onde'. The product also can be choosed base on customer's desire, but in this first business we provide the 'onde-onde' with five flavours - Chocolate, White Chocolate, Apple Jam, Blackcurrent Jam, and Strawberry Jam. The location for our outlet is at University Apartment 1. From the location chosen, we believe that it is a strategic place to attract customers which we are targeting school and university students, teenagers and working people that can enjoy their 'onde-onde'. The differences of our product may bringing satisfaction, happiness, and joy to customer whom we also come out with other alternatives to serve it on attractive packaging, variety of delicious flavours, condition of the outlet and the customer service provide by our staff.